Management of Principal Leadership in Improving Teacher Performance to Optimize the Quality of Education at Tenggarong Elementary School - Basuni; Komariyah, Laili; Nurlaili (Borneo Educational Journal (Borju), 2025)
An effective school principal must possess good leadership skills to create a conducive learning environment, develop teacher competencies, and ensure that the learning process runs smoothly. This study aims to describe the planning, organizing, implementation, and supervision carried out by the principal in improving teacher performance to maximize the quality of education at Muhammadiyah 1 Elementary School in Tenggarong. This research uses a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews, and documentation, with data validity checks through source and method triangulation. The results indicate that at the planning stage, Muhammadiyah 1 emphasizes strengthening religious values and utilizing technology in learning; at the organizing stage, a deliberative approach is used with support from Muhammadiyah institutions; at the implementation stage, the focus is on religious activities and the use of technology to create a dynamic and interactive learning environment; and at the supervision stage, it is conducted through structured evaluations, classroom observations, and regular evaluation meetings. By implementing the results of this research, it is hoped that a better and more competitive educational environment can be created, capable of producing a higher quality generation.